2022
DOI: 10.1002/celc.202101632
|View full text |Cite
|
Sign up to set email alerts
|

Linker‐Modulated Peroxide Electrosynthesis Using Metal‐Organic Nanosheets**

Abstract: The electrochemical synthesis of hydrogen peroxide (H 2 O 2 ), a widely used oxidant, is emerging as a green alternative to the conventional anthraquinone method. In this work, Ni-based metal-organic nanosheet (NiÀ MON) catalysts constructed using a variety of linkers were studied as oxygen reduction catalysts. Using a host of analytical techniques, we reveal how modulating the terephthalic acid linker with hydroxy, amine, and fluorine groups impacts the resulting physical and electronic structure of the Ni ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The effect of linkers was also used to modulate the reactivity of Ni-based 2D sheets used for oxygen reduction to peroxide, a widely used chemical oxidant. 88 A hypothesis was that amine-functionalized linkers weakened the binding of *OOH on the Ni active sites and thereby promoted the desorption of the desired product (partial current densities of up to 200 mA cm −2 ) instead of over-reduction to H 2 O in a GDE alkaline flow cell setup.…”
Section: Molecular Catalyst Containing Extended Systemsmentioning
confidence: 99%
“…The effect of linkers was also used to modulate the reactivity of Ni-based 2D sheets used for oxygen reduction to peroxide, a widely used chemical oxidant. 88 A hypothesis was that amine-functionalized linkers weakened the binding of *OOH on the Ni active sites and thereby promoted the desorption of the desired product (partial current densities of up to 200 mA cm −2 ) instead of over-reduction to H 2 O in a GDE alkaline flow cell setup.…”
Section: Molecular Catalyst Containing Extended Systemsmentioning
confidence: 99%
“…Electrically conductive metal–organic frameworks (MOFs) offer a way to bridge this gap, as they are molecularly defined and are both intrinsically porous and conductive . They are fundamentally distinct from electrocatalysts made from sacrificial MOF precursors (such as single-atom catalysts accessed via thermolysis or electrolytic degradation of MOFs), because they retain their molecular definition. ,,,, As such, the structure space available to conductive MOFs renders them an ideal platform to tune the atomic structure for performance. We and others have previously shown that a family of 2D MOFs with the general formula M 3 (HITP) 2 (HITP = 2,3,6,7,10,11-hexaiminotriphenylene, M = Co, Cu, Ni) (Figure A) are active for the O 2 electroreduction reaction (ORR), a transformation central to H 2 O 2 electrosynthesis, metal/air batteries, and fuel cells. ,, These and other conductive MOFs typically exhibit intrinsic surface areas (∼300–900 m 2 g –1 ) at least 10 times larger than that of dense metallic nanoparticles and conductivities comparable to that of graphite, yet their geometric current densities for ORR rarely exceed −1 mA cm –2 , implying a surprisingly low intrinsic electrocatalytic activity. ,,,, …”
Section: Introductionmentioning
confidence: 99%